2022
DOI: 10.1080/0886022x.2022.2085576
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of leflunomide combined with corticosteroids for the treatment of IgA nephropathy: a Meta-analysis of randomized controlled trials

Abstract: Objective We performed a meta-analysis of randomized controlled trials (RCTs) to evaluate the efficacy and safety of leflunomide combined with corticosteroids, compared with corticosteroids alone, for IgA nephropathy. Materials and methods Studies were retrieved by searching of PubMed, Embase, Cochrane’s Library, China National Knowledge Infrastructure (CNKI), and Wanfang databases on 11 October 2021. A random-effect model incorporating the heterogeneity was used to poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Besides that, combination protocols that include leflunomide have shown significant advantages in efficacy and safety. Lv et al [ 28 ] reported the beneficial effects of combined treatment with leflunomide and corticosteroids for IgAN. In an RCT, Cheng et al [ 15 ] demonstrated that valsartan combined with clopidogrel and leflunomide could protect renal function with minimal adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, combination protocols that include leflunomide have shown significant advantages in efficacy and safety. Lv et al [ 28 ] reported the beneficial effects of combined treatment with leflunomide and corticosteroids for IgAN. In an RCT, Cheng et al [ 15 ] demonstrated that valsartan combined with clopidogrel and leflunomide could protect renal function with minimal adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies [ 28 ], our study focuses more on the safety and efficacy of low-dose corticosteroids combined with leflunomide in treating progressive IgA nephropathy. In addition, our study also found that the low-dose corticosteroids combined with leflunomide significantly reduced UPE and the incidence of serious adverse events, which was not mentioned in the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous, really extensive meta-analyses [30,31] describing the possible role of leflunomide in IgAN, suggested its efficacy in improving renal function and decreasing proteinuria, mostly when combined with CS.…”
Section: Leflunomidementioning
confidence: 99%
“…Lvet al [31], presented a different meta-analysis of19 RCTs (7 included in previous meta-analyses) including 1153 patients randomly assigned to a treatment group of the combined therapy with leflunomide and CS or CS alone. The combined treatment with leflunomide + CS is more effective than CS alone in reducing proteinuria and preserving renal function.…”
Section: Leflunomidementioning
confidence: 99%